Web-Based Management Information System for Pesantren Muhammadiyah - Harahap, Dewi Estri Jayanti; Imamudiroyah, Mohammad Khoyyinudin (Yayasan Mitra Peduli Indonesia, 2024)
The Pesantren Muhammadiyah Development Institute (LP2M) is in charge of data management, licensing, and management of Pesantren Muhammadiyah, but it still manually processes Islamic boarding school databases. This often causes several problems, including time, process, and reporting. Data changes are relatively long, and the level of accuracy could be higher. One of the database management systems considered the most relevant is implementing a web-based management information system for Pesantren Muhammadiyah. The implementation of this website-based management information system can be accessed easily, quickly, and accurately. This implementation uses the development Life Cycle (SDLC) development methodology or the Waterfall model. The Waterfall method helps input Islamic boarding school data and makes it easier to register or change it quickly, efficiently, and accurately. PHP as a scripting language, Xampp web server, and MySql as a database are the tools needed to design this application. The results of this study were successfully presented with 85% usability. They provided convenience for LP2M in processing and managing the Pesantren Muhammadiyah database accurately, quickly, and precisely, making it easier to provide services and make decisions or improve data effectively and efficiently.